The Role of Zakat and Waqf in Encouraging Sustainable Economic Growth - Habibi, Rahmat (Journal of Islamic Economy, 2024)
This study aims to examine the role of zakat and waqf in driving sustainable economic growth with a focus on their contribution to wealth redistribution and socio-economic empowerment. The research method used is the Systematic Literature Review (SLR), which allows the collection and analysis of relevant studies published in the last five years (2019–2024) from various leading academic databases, such as Scopus, Web of Science, Google Scholar, and ProQuest. The SLR process involves several stages, starting from formulating research questions, developing literature search strategies, screening articles based on inclusion and exclusion criteria, to synthesizing key findings. The results of the study indicate that zakat and waqf play a significant role in driving sustainable economic growth through wealth redistribution mechanisms and socio-economic empowerment, with greater contributions when optimized through digitalization and management innovation. The synergy between zakat, waqf, and the national financial system as well as strengthening regulations and public literacy are key factors in increasing their impact. This study emphasizes the importance of cross-sectoral cooperation to ensure that zakat and waqf can be the main driving force in realizing fair, inclusive, and sustainable economic development.